SISTEM INFORMASI LOKASI PARKIR KOSONG MENGGUNAKAN SENSOR LDR DAN INFRAMERAH BERBASIS VISUAL DI GEDUNG PARKIR RSUD TUGU REJO SEMARANG - Arifan Ikha Putra (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Vehicle movements that occur have begun and ended in the parking lot. Such conditions will certainly require adequate parking spaces, but the availability of parking spaces in the city center is usually very limited, a problem that often arises when looking for an empty parking location is that we must surround a very large and limited parking space to find a parking location that is still empty, and of course causing less efficiency of time wasted just to find a parking location that is still empty The information system in this study serves to display parking location availability information to parking users. By designing a prototype for parking monitoring using (a) LDR (Light Dependent Resistor) and (b) Infrared sensors as input, (c) arduino uno as a microcontroller and interface for visual-based monitoring and using a counter system at the entrance and exit side to count the number of cars inside a parking lot. The availability of this information system aims to notify vehicle users about the availability of parking locations so that users can decide whether to enter the parking building or look for another parking building. The results achieved are a prototype information system for parking location availability that can display information on a monitor screen. Information displayed on the monitor screen is in the form of a web that contains used and empty parking spaces,